IDENTIFICATION OF POTENTIAL AND DEVELOPMENT OF MEDIUM SMALL-MEDIUM ENTERPRISES (UMKM) IN CELAWAN VILLAGE, BEACH MIRROR DISTRICT, SERDANG DISTRICT, NORTH SUMATERA PROVINCE - Simon, Jhon; Nasution, Farida Hanum; Hasoloan, Aswand (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2020)
Micro, Small and Medium Enterprises (MSMEs) have a strategic role in national economic development. MSMEs play a role in economic growth and employment as well as in the distribution of development results. The objectives of the study are: (1) To identify the potential of the area in Celawan Village, Pantai Cermin District, Serdang Bedagai Regency, North Sumatra Province, and (2) Formulate the MSME strategy and development program in Celawan Village. Data collection techniques used are using in-depth interviews, observation, and documentation study. The method used is a qualitative research method with a descriptive approach. The benefit of this idea is expected to be able to help the community, government, researchers and academics in planning the latest programs that contribute greatly to the State. Therefore, Micro, Small and Medium Enterprises (MSMEs) have an important role in the local local economy in driving economic activity to the international level. In the framework of implementing, planning, empowering, and developing Micro, Small and Medium Enterprises (MSMEs) regulations from the government that are needed to provide opportunities for developing MSMEs in rural areas including improvement of facilities and infrastructure, banking access, human resource development, Business Network Development, Marketing and Business Partnership and better economic climate improvement to support the existence of the community facing economic competition in the midst of global markets